PROPERTIES OF POLYMER COMPOSITES FILLED WITH SIO2, ZNO AND MG(OH)(2) NANO POWDER. - (:unkn) unknown (INEGI-INST ENGENHARIA MECANICA E GESTAO INDUSTRIAL, 2012)
Thermoplastic resin-mineral filler composites have been widely used in molded products due to effective cost reduction. Generally, the addition of mineral fillers will have an embrittling effect on polymers although the rigidity of the polymers can be increased. Much effort has been devoted to improving the properties of polymers by the addition of inorganic fillers, such as SiO2, ZnO, CaCO3 and Mg(OH)(2). In this study, mechanical properties of the high density polyethylene (HDPE) composites filled with silicon dioxide (SiO2), zinc oxide (ZnO) magnesium hydroxide [Mg(OH)(2)] and calcium carbonate (CaCO3) were investigated. The structure and properties of the composites are characterized using a scanning electron microscopy (SEM) and Energy dispersive X-ray spectroscopy (EDS). Furthermore, HDPE composites were subjected to examinations to obtain their tensile strengths, yield strengths, elasticity modulus, % elongation, Izod impact strength, hardness, heat deflection temperature (HDT), Vicat softening point and melt flow index (MFI).
Keywords: silikon dioxide; zinc oxide; magnesium hydroxide; calcium carbonate; DYNAMIC MECHANICAL-PROPERTIES; LOW-DENSITY POLYETHYLENE; CALCIUM-CARBONATE; POLYPROPYLENE; BEHAVIOR